2010
DOI: 10.1371/journal.pone.0010853
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Couples Hematopoiesis with Bone Formation

Abstract: BackgroundIt is well established that bleeding activates the hematopoietic system to regenerate the loss of mature blood elements. We have shown that hematopoietic stem cells (HSCs) isolated from animals challenged with an acute bleed regulate osteoblast differentiation from marrow stromal cells. This suggests that HSCs participate in bone formation where the molecular basis for this activity is the production of BMP2 and BMP6 by HSCs. Yet, what stimulates HSCs to produce BMPs is unclear.Methodology/Principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
200
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(221 citation statements)
references
References 28 publications
18
200
3
Order By: Relevance
“…In 2008, they showed that hematopoietic stem cells (HSCs) are capable of inducing osteogenic differentiation of murine MSCs via paracrine stimulation with bone morphogenetic protein 2 and 6 (BMP-2, BMP-6) (Jung et al 2008). This finding was substantiated in a subsequent paper which demonstrated that EPO activates JAK/STAT signaling in HSCs leading to BMP secretion (Shiozawa et al 2010). In that study, daily EPO injections of 1500-6000 IU/kg for 28 days increased bone volume and the number of osteoblasts and osteoclasts in mice.…”
Section: Epo and Bonementioning
confidence: 62%
See 2 more Smart Citations
“…In 2008, they showed that hematopoietic stem cells (HSCs) are capable of inducing osteogenic differentiation of murine MSCs via paracrine stimulation with bone morphogenetic protein 2 and 6 (BMP-2, BMP-6) (Jung et al 2008). This finding was substantiated in a subsequent paper which demonstrated that EPO activates JAK/STAT signaling in HSCs leading to BMP secretion (Shiozawa et al 2010). In that study, daily EPO injections of 1500-6000 IU/kg for 28 days increased bone volume and the number of osteoblasts and osteoclasts in mice.…”
Section: Epo and Bonementioning
confidence: 62%
“…Furthermore, these authors were the first to describe a direct osteogenic effect on MSCs and osteoclasts. While EPO increased the number of osteoclasts, it impaired their function via down-regulation of cathepsin K which resulted in net bone formation (Shiozawa et al 2010;Kim et al 2012). In their setting, 20 IU/ml EPO increased the osteogenic differentiation of hMSCs about 1.7-fold compared with the positive control group estimated with alizarin red staining (AZR) after 21 days (Kim et al 2012).…”
Section: Epo and Bonementioning
confidence: 99%
See 1 more Smart Citation
“…However, recent data demonstrated that tumor cells compete with HSCs for niche occupancy, thus the presence of HSCs can negatively regulate tumor metastasis to bone [40]. More interestingly, HSCs have been shown to increase bone morphogenetic proteins (BMP)-2 and 6 in response to erythropoietin stimuli, potentially contributing to augmented osteoblastogenesis [97]. These data collectively support that even a single cell population entity (i.e.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, several studies indicated a positive correlation between enhanced erythropoiesis and osteoclastogenesis [56,58].…”
Section: Discussionmentioning
confidence: 96%